Ritual and socio-economic change: The Aymara case - Arnold, Simón Pedro (1995)
This communication is located in the broader framework of an ongoing investigation, not only in the Aymara and Andean context, but also in a comparative way in Rwanda, Burundi and Ghana. The problem proposed here is based on a finding that has been quite common for many years in the field of social sciences: the different models and attempts at development implemented for thirty years in the so-called "Third World" countries often turn out to be a failure. In this regard, the researchers find one of the possible explanations —and at the same time one of the symbolic-religious meanings for understanding and managing the socio-economic reality of a given people.